(untitled) (KULT_online, 2014)
The handbook Phantastik makes the theory of the fantastic accessible. It has a diachronic, transnational, interdisciplinary perspective that takes into account the diverging traditions of the various language departments. Additionally, it presents a plethora of aspects relevant to research in the fantastic. It presents concisely the many strands of research in the fantastic. Thus, it can be a very good starting point for further research.